Sustainable Development Goals (SDGS) and Total Cost of Ownership (TCO): a holistic approach - Stroparo, Telma Regina (2024)
Objective: This study aims to explore the concepts and applicability of the Total Cost of Ownership (TCO) tool in strategies aligned with the Sustainable Development Goals (SDGs). Method: The analysis focused on the implementation costs of projects and processes on a rural property undergoing agroecological transition. Visible and hidden costs were identified and quantified using the TCO technique within this context. These costs were aligned with agroecological principles and the SDGs, aiming for economic self-sufficiency, operational cost reduction, enhanced efficiency, and greater resilience to future risks. Results: Opportunities were identified for improving economic self-sufficiency, reducing operational costs, and enhancing efficiency. Moreover, including subjective and hidden costs provided a comprehensive understanding of the social and environmental impacts of projects, products, or processes. Conclusions: Based on the findings, we conclude that applying the TCO tool in strategies aligned with the SDGs is an effective approach to promote economic self-sufficiency, environmental sustainability, and social inclusivity. Holistic assessment, integrating social, environmental, political, and cultural dimensions, contributes to safeguarding knowledge, practices, traditions, and biodiversity. Additionally, it fosters a sense of belonging, improves quality of life, supports sustainable development, and enhances local governance in family farming-oriented rural properties.